Factors Associated with Mortality in ST-segment Elevation Myocardial Infarction Patients of Hospitals in Thailand - วิชัยเรืองธรรม กิติกร; จารุจิตติพันธ์ พิศมัย; วีระญาณนนท์ เกียรติชัย (Thai Interdisciplinary and Sustainability Review, 2021)
The objectives of this study were to investigate the mortality rate among patients with acute ST-segment elevation myocardial infarction (STEMI) patients and to study the mortality rate according to various hospital factors, including the study of various hospital factors affecting the mortality rate of STEMI patients in Thailand. The secondary data was collected from 1,180 hospitals in Thailand and analyzed by descriptive and inferential statistics. The differences between variables were conducted by one-way ANOVA and the relationship between variables was conducted by multiple regression analysis. The results showed that Thailand still has faced both shortage and improper concentration of cardiac catheterization centers. The overall STEMI mortality rate is 8.46%, in the aspect of the health service area, the areas that did not pass the mortality rate criteria (less than 10 %) have been still the same as previous (health service areas 2, 3, and 4). The mortality rate are statistically significant higher among long-established and government hospitals. The relationship between various factors of hospital including the number of beds, the established period, proportion of the number of cardiac catheterization centers, type of hospital and the existence of cardiac catheterization center to the mortality rate, by multiple regression analysis have shown that various hospital factors jointly predict trends of the mortality rate at a low level, 6 percent (adjusted R2 = 0.062).The results suggest that the Ministry of Public Health in addition to provide and allocate more cardiac catheterization centers across the country, should develop a better referral system for STEMI patients especially in 2th, 3rd and 4th health service areas, long-established, and government hospitals where still face problems.